Securing SQL Server : DBAs defending the database - Carter, Peter A. (Apress, 2018)
Providing practical advice and engaging examples, this book will help you protect your data from attack by using SQL Server technologies to implement a defense-in-depth strategy, perform threat analysis, and encrypt sensitive data as a last line of defense against compromise. --